A Geomimetic Approach to the Formation and Identification of Fossil Sterane Biomarkers in Crude Oil: 18-nor-D-homo-Androstane and 5a,14ß-Androstane. - Bender, M.; Schmidtmann, M.; Summons, Roger; Rullkötter, J.; Christoffers, J. (Wiley - V C H Verlag GmbH & Co. KGaA, 2015)
A diazonium ion derived from 18-aminoandrostane rearranged upon decomposition by a carbonium and a carbenium ion to furnish a mixture of a cyclopropanated compound and two D-homo-androstenes. Hydrogenation of this mixture gave the saturated hydrocarbons, 18-nor-D-homo-androstane and 5a,14ß-androstane, which are both fossil sterane biomarkers in Neoproterozoic crude oil. The so far unknown constitution and configuration as well as the geochemical genesis were established by this experiment. The starting material for this investigation, 18-aminoandrostane, was prepared in twelve steps from androstan-17-one (12.5% overall yield) with a Barton reaction as the key step.